Predictive Factors for Discharge Destination Following Posterior Lumbar Spinal Fusion: A Canadian Spine Outcome and Research Network (CSORN) Study. Issue 4 (June 2019) - Morcos, Mina W.; Jiang, Fan; McIntosh, Greg; Ahn, Henry; Dea, Nicolas; Abraham, Edward; Paquet, Jerome; Natara, Andrew; Johnson, Michael; Manson, Neil; Fisher, Charles; Rampersaud, Raja; et al.
Study Design: Ambispective cohort study. Objective: Patients spend on average 3 to 7 days in hospital after lumbar fusion surgery. Patients who are unable to be discharged home may require a prolonged hospital stay while awaiting a bed at a rehabilitation facility, adding cost and imposing a considerable burden on the health care system. Our objective is to identify patient or procedure related predictors of discharge destination for patients undergoing posterior lumbar fusion. Methods: Analysis of data from the Canadian Spine Outcomes and Research Network. Patients who underwent lumbar fusion for degenerative pathology between 2008 and 2015 were identified. Multivariable logistic regression analysis was used to identify independent predictors of the discharge destination. Results: A total of 643 patients were identified from the database, 87.1% of the patients (N = 560) were discharged home while 12.9% (N = 83) required discharge to nonhome facilities. Using multivariate logistic regression analysis, the predictors for discharge to a facility rather than home were identified including: increasing age (odds ratio [OR] 1.045, 95% confidence interval [CI] 1.017 -1.075, P < .002), increasing body mass index (BMI) (OR 1.069, 95% CI 1.021 -1.118, P < .004), increasing disability score (OR 1.025, 95% CI 1.004 -1.046, P < .02), living alone preoperatively (OR 1.916, 95% CI 1.004-3.654, P < .05), increasing operating time (OR 1.005, 95% CI 1.003 -1.008, P < .0001), need for blood transfusion (OR 3.32, 95% CI 1.687-6.528, P < .001), and multilevel fusion surgery (OR 1.142, 95% CI 1.007 -1.297, P < .04). Conclusions: Older age, high BMI, living alone, high disability score, extended surgical time, blood transfusion, and multilevel fusion are significant factors that increase the odds of being discharged to facilities other than home. Level of Evidence: Level 3.